(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Background: Escherichia coli is the major bacterial pathogen being isolated and reported from urine, globally. For these uropathogens the therapeutic management becomes limited, so knowledge about the antimicrobial resistance pattern of these agents at a specific area may help the doctors to choose correct treatment regimen. The aim of the current study was to detect the common uropathogens from urine and the antimicrobial susceptibility pattern of Escherichia coli in Dhaka Medical College Hospital (DMCH). Methods: Samples were collected over a period of 12 months from July 2011 to June 2012 from the patients of DMCH irrespective of age and sex. Samples were cultured in blood agar and MacConkey agar media and organisms were identified by different biochemical tests such as oxidase test, reaction in MIU and simmon’s citrate media and different sugar fermentation tests. Data were analyzed using Microsoft Excel (2007). Results: From total 300 urine samples, 177 (59%) Gram-positive and Gram-negative bacteria were isolated. Among them, Esch. coli was the most predominant 112 (63.28%) organism followed by Enterobacter spp. (11.87%). The prevalence of Esch. coli was significantly higher in females (63.39%) of younger age group than in males (36.61%). Esch. coli was highly sensitive to imipenem (100%) followed by ceftriaxone (62.50%), ceftazidime (55.36%) and azitromycin (35.72%) respectively. Low sensitivity patterns were found against doxycycline (13.39%), co-trimoxazole (16.07%), amoxiclav (21.43%) and ciprofloxacin (23.22%) respectively. Conclusion: The result of this study provides insight into the high proportion of multidrug resistant Escherichia coli and creates a need to report them routinely in laboratories. Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 40-44